An insight into the role of carbon dots in the agriculture system: a review. Issue 4 (15th March 2023) - Maholiya, Anju; Ranjan, Pushpesh; Khan, Raju; Murali, S.; Nainwal, Rakesh C.; Chauhan, Puneet S.; Sathish, N.; Chaurasia, J. P.; Srivastava, Avanish K.
Abstract : CDs in sustainable agricultural production can significantly aid in meeting global food demand while maintaining environmental resilience. Abstract : Sustainable agricultural production can significantly aid in meeting global food demand while maintaining environmental resilience. Nanotechnology has garnered immense attention as a sustainable approach to addressing the challenges faced by the agricultural sector. Carbon dots (CDs) are novel carbon nanomaterials having unique properties. They have a small size with a core–shell-like structure and exhibit tunable photoluminescence (PL) similar to quantum dots (QDs). CDs additionally possess high aqueous solubility, biocompatibility, and negligible toxicity. Considering their remarkable bio-compatibility, CDs are relatively safer nanomaterials for application in agriculture. In recent years, CDs have shown significant growth-enhancing effects on plants. As agricultural yields rely on the photosynthetic efficiency of plants, CDs with their PL can augment photosynthesis and utilize solar energy efficiently for increasing crop productivity, making them effective photosynthetic enhancers. In addition to PL, the hydrophilicity of CDs also enhances plant growth by accelerating seed germination and water absorption by plants. Moreover, their antimicrobial and antioxidant properties assist them to relieve biotic and abiotic stresses, improving plant health. Thus, CDs' application would help enhance plant growth substantially. CD-based agricultural sensors can also detect herbicides and pesticides, which supports the future development of smart sensors. This review presents the broad application of CDs in agriculture as seed priming agents, photosynthetic enhancers, plant stress ameliorators, and sensors. This review also discusses the green synthesis and properties of CDs. Lastly, the challenges and future perspectives on the potential use of CDs in the agricultural system have been discussed.